Perceived barriers to the adoption of low-carbon energy in the South African Energy-Intensive Industry - Muditambi, Lydia (My University, 2021)
Carbon dioxide is the predominant greenhouse gas associated with the combustion of fossil fuels. Energy-intensive industry is linked to high carbon emissions due to high energy consumption compared to other types of industry, hence the need for low-carbon energy options. With local and international pressure to reduce carbon emissions, this study seeks to explore the available options to facilitate low-carbon energy and to identify the barriers associated withtheir adoption within the South African energy-intensive industry. Most previous studies on this topicwere conducted for industrialized countries, and this study focus on understanding the barriers that affect South Africa and possibly other developing countries. Quantitative approach was employed using online survey and descriptive statistics to gather and analyse information on low-carbon energy options available and employed within the South African energy-intensive industry and to understand the barriers to their adoption. The study found that regulatory, economic, facility structural design, and culture and behavioural barriers exist in the South African energy-intensive industry. The barriers identified provides the basis for planning and resource allocation for the energy-intensive industry
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Energy Leadership), 2021
Keywords: Anthropogenic Carbon dioxide emissions; Barriers to adoption; Carbon emissions; Climate Change; Energy consumption; Energy Intensive Industry (EII); Industrial Sector; Low-carbon energy; SDG-7: Affordable and clean energy